2012
DOI: 10.1891/1946-6560.3.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Bidirectional Versus Unidirectional Intimate Partner Violence Across Samples, Sexual Orientations, and Race/Ethnicities: A Comprehensive Review

Abstract: One hotly debated topic within the field of intimate partner violence (IPV) is the degree to which IPV can be understood as primarily a unidirectional versus bidirectional phenomena; this topic forms a key component of the gender symmetry versus asymmetry of domestic violence debate. Resolution of this controversy has important prevention and intervention implications. In the current study, a comprehensive review of the literature was conducted, and 48 studies that reported rates of bidirectional versus unidir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

46
275
2
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(331 citation statements)
references
References 73 publications
46
275
2
8
Order By: Relevance
“…Straus, 2008;Langhinrichsen-Rohling et al, 2012), it is in contrast to the more traditional and gendered approaches to studying IPV. Whilst patriarchy could be an explanation of some men's violence towards women (though it seems a small proportion), it is unlikely to be the main etiological factor influencing women's IPV, and especially so when IPV is mutual within the relationship.…”
Section: Implications Of Overlooking Bidirectional Violencementioning
confidence: 99%
See 3 more Smart Citations
“…Straus, 2008;Langhinrichsen-Rohling et al, 2012), it is in contrast to the more traditional and gendered approaches to studying IPV. Whilst patriarchy could be an explanation of some men's violence towards women (though it seems a small proportion), it is unlikely to be the main etiological factor influencing women's IPV, and especially so when IPV is mutual within the relationship.…”
Section: Implications Of Overlooking Bidirectional Violencementioning
confidence: 99%
“…Whilst patriarchy could be an explanation of some men's violence towards women (though it seems a small proportion), it is unlikely to be the main etiological factor influencing women's IPV, and especially so when IPV is mutual within the relationship. When both members of the couple are being aggressive then it suggests causes could be in dyadic areas, for example around conflict management (Langhinrichsen-Rohling et al, 2012). It further highlights the importance of considering women's aggression in uni-or bidirectional relationships.…”
Section: Implications Of Overlooking Bidirectional Violencementioning
confidence: 99%
See 2 more Smart Citations
“…Second, only two studies to our knowledge have examined the prevalence and correlates of women's IPV perpetration during pregnancy and postpartum (Hellmuth, Gordon, Stuart, & Moore, in press;Tzilos, Grekin, Beatty, Chase, & Ondersma, 2010). Both studies found that like many women in non-expectant populations (see Langhinrichsen-Rohling, Selwyn, & Rohling, 2012, for review), some pregnant and postpartum women use psychological and physical IPV as frequently and severely as they experience IPV victimization. However, neither of these studies examined women's sexual IPV perpetration.…”
mentioning
confidence: 99%